#### Answer

$x=-2\pm\sqrt{11}$

#### Work Step by Step

$(x+5)(x-1)=2$
Evaluate the product on the left side of the equation:
$x^{2}+4x-5=2$
Take the $2$ to the left side:
$x^{2}+4x-5-2=0$
Simplify the equation by combining like terms:
$x^{2}+4x-7=0$
Use the quadratic formula to solve this equation. The formula is $x=\dfrac{-b\pm\sqrt{b^{2}-4ac}}{2a}$. Here, $a=1$, $b=4$ and $c=-7$
Substitute:
$x=\dfrac{-4\pm\sqrt{4^{2}-4(1)(-7)}}{2(1)}=\dfrac{-4\pm\sqrt{16+28}}{2}=...$
$...=\dfrac{-4\pm\sqrt{44}}{2}=\dfrac{-4\pm2\sqrt{11}}{2}=-2\pm\sqrt{11}$